Boarder-Focus-Challenges of School Feeding Service in Edo State: Implications for School Health Education - Obasuyi, Osato Harriet; Igudia, Enoma O (NIU Journal of Social Sciences, 2020)
It is the responsibility of school authorities that have boarding system to promote the health and avoid malnutrition of their learners through adequate school feeding service. It is a common reality that some boarding schools hardly meet these standards. The study, therefore, assessed the challenges of school feeding services in Edo State by determining boardersâ€™ level of preference of school food, among other variables. Five research questions and one hypothesis were assessed by the study. The study was descriptive and from a population of 1755 secondary school boarders, 317 of them were randomly selected as sample for the study. A validated self-structured Challenge of School Feeding Service (Boarders) Questionnaire (CSFSQ) with a reliability coefficient of 0.73 was used to collect data from the respondents. Results showed that private and public secondary school boarders have low preference for school meals because food is improperly cooked and not tasty, does not contain all classes of food, is sometimes served late and kitchen store/dining hall is not always clean, the quantity of food is poor, cooks sometimes do not wear aprons or headgears and their fingers or skin are unkempt. It was recommended, based on findings that food handling guidelines covering personal cleanliness, preparation, storage and serving of meals be provided to each food vendor while equally displaying same in the central kitchen.  Keywords: boarder; challenges; school; feeding; service; school; health; education